Ideal vs. reality: evidences from senior teachers’ experiences on the Malaysian School-based Assessment system (SBA) - Hashim, Che Noraini; Ariffin, Adlina; Muhd Hashim, Nurhidayah (2013)

(untitled)
School-based Assessment (SBA) system or better known by its Malay acronym as PBS (Pentaksiran Berasaskan Sekolah), being part of the Malaysia educational reform, was officially introduced by the Ministry of Education in 2011 with the aim to improve the effectiveness of the system in evaluating students’ academic progress and personal development. Under the system, students’ learning outcomes will be evaluated based on their competencies and readiness and teachers are encouraged to use various evaluation methods such as question and answer sessions, quizzes, presentation, short writing, dramas, and role-playing (Dietel, Herman & Knuth, 1991; Davison, 2007). However, the system received many negative feedbacks and claimed to pose great pressures on the part of the teachers, students and their parents as well. This study aspires to investigate the issue of SBA based on evidences revealed by senior teachers from five secondary schools who were involved in the implementation of the system. The qualitative case study aimed at identifying some perceptions, expectations, challenges and suggestions to improve the implementation of the SBA. Respondents perceived that teachers had been imposed with additional workloads in terms of paper work on top of their teaching responsibilities. Furthermore, large class size and lack of supporting resources (e.g. internet facilities) had further aggravated their negative perceptions on the SBA system. Overall they strongly admitted that both students and teachers did not receive much benefit from the system. The findings indicate that to ensure the effectiveness of the system’s implementation, teachers must be equipped with sufficient and detailed information on the evaluation process for a specified students’ competency meant to be evaluated. In doing so, fears and negative attitudes among teachers on the SBA shall be allied. Besides that, a more effective mechanism needs to be developed to reduce the burden of teachers in preparing and completing documentation as required by the SBA, while issues such as heavy teaching hours and large class size be promptly addressed.